Blood Vessel Density in Basal Cell Carcinomas and Benign Trichogenic Tumors as a Marker for Differential Diagnosis in Dermatopathology. (16th September 2010) - Winter, Julia; Kneitz, Hermann; Bröcker, Eva-B.
Abstract : In order to get insight into the density of blood vessels in the stroma of benign and malignant trichogenic neoplasms, immunohistological quantification of CD 31 positive vessels was performed in 112 tumors, comprised of 50 BCCs of nodular (35) or morphoeic (15) growth patterns, 17 Pinkus' tumors, as well as 17 trichoepitheliomas of which 6 were desmoplastic, 8 trichofolliculomas, and 20 trichoblastomas. Methods . Vessel density was counted within the tumors, in the tumor-surrounding stroma, and, as a control, in the normal skin of the operation specimen. The results were compared using statistical methods. Results . Whereas, irrespective of the patients' age and location of tumors, the vessel density in normal skin showed no significant differences (8.8 ± 2.7 ), the counts in the peritumoral stroma revealed significant differences between the different tumors investigated. The highest counts were obtained in BCC (24.7 ± 6.7 ) and the lowest in benign trichogenic neoplasms (around 14) Pinkus' tumors revealed intermediate counts (19.7 ± 6.6 ). The vessel densities within the tumors were generally low, and no correlation to the dignity was found. Conclusion . Determination of blood vessel density in the peritumoral stroma may be an additional parameter for differential diagnosis of trichogenic tumors of uncertain dignity.